2010
DOI: 10.1111/j.1540-8159.2009.02609.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Isolation of the Pulmonary Veins Using the PVAC Catheter

Abstract: (1) PVAC-guided ablation (i.e., mapping and ablation with a single catheter) results in isolation of all PVs in 73% of the patients. (2) An additional circular mapping catheter is required to increase complete isolation rate to 93% of the patients. (3) Given the esophageal T degrees rise in almost 50% of patients, safety precautions are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…This is also observed with the HDMA catheter and the cryoballoon [9,10]. However, in case of a common ostium or when early branching is present, the guidewire can be positioned in different side branches of the PV resulting in different PVAC positions, creating overlapping ablation lines that as a whole result in a more wide circumferential PVI [8].…”
Section: Procedures Performance Of the Pvacmentioning
confidence: 93%
See 4 more Smart Citations
“…This is also observed with the HDMA catheter and the cryoballoon [9,10]. However, in case of a common ostium or when early branching is present, the guidewire can be positioned in different side branches of the PV resulting in different PVAC positions, creating overlapping ablation lines that as a whole result in a more wide circumferential PVI [8].…”
Section: Procedures Performance Of the Pvacmentioning
confidence: 93%
“…Mansour et al [5] presented that 12% of the veins which seemed isolated on the HDMA, were not isolated on a regular circular mapping catheter. The other study showed that PVAC has a diagnostic accuracy of 95% [8]. Authors suggested that bipolar electrograms are less detailed (most likely due to larger electrode size) but allowed to correctly diagnose PVPs.…”
Section: Procedures Performance Of the Pvacmentioning
confidence: 99%
See 3 more Smart Citations